The impact of tumor budding on tumor biology in patients with hepatocellular carcinoma - Duran, Osman Firat; Gokcan, Hale; Kiremitci, Saba; Aras, Nermin; Karayel, Sevinc Tugce; Yilmaz, Volkan; Idilman, Ramazan (Elsevier, 2024)
[Abstract Not Available]
European-Association-for-the-Study-of-the-Liver Congress (EASL) -- JUN 05-08, 2024 -- Milan, ITALY